Pertumbuhan Dan Hasil Tanaman Terung Ungu (Solanum melongena L.) Pada Berbagai Dosis Pupuk NPK Dan Konsentrasi POC Sabut Kelapa - Aufa Anindita; Ellen Rosyelina Sasmita (Jurnal Agro Wiralodra, 2026)
Purple eggplant productivity is still relatively low and has not been able to meet market demand, so efforts are needed to increase production through fertilization. The study aims to determine the growth and yield of purple eggplant plants at various doses of NPK fertilizer and coconut fiber POC concentration. The study used a Completely Randomized Design (CRD) with 2 factors + 1 control with 3 replications. The first factor was the dose of NPK fertilizer, namely 10, 13, and 16 g/plant. The second factor was the concentration of coconut fiber POC, namely 50, 75, and 100 mL/L. The control used NPK fertilizer at a dose of 20 g/plant. Data were analyzed using a 5% analysis of variance (ANOVA) and continued with a 5% DMRT test. Differences between treatments and controls were analyzed using the Orthogonal Contrast Test. The results showed that there was an interaction between plant height (42 days after planting) and flowering time. Application of NPK fertilizer at a dose of 13g/plant produced the best results in terms of fruit length and fruit weight per fruit. Meanwhile, application of coconut fiber POC at a concentration of 75 mL/L produced the best results in terms of plant height at 28 days after planting, number of leaves (21 and 28 days after planting), stem diameter (42 days after planting), fruit diameter, fresh fruit weight per plant, and harvest index. The combination of treatments was significantly better than the control in plant height (21 days after planting), number of leaves (21 days after planting), flowering time, number of eggplant fruits per plant, fruit diameter, fresh fruit weight per plant, and harvest index.